Pendampingan Penyusunan Portofolio Kampunge Arek Suroboyo Ramah Perempuan dan Anak (KAS-RPA) di RW 04 Kelurahan Gundih, Kecamatan Bubutan, Kota Surabaya - Astri Fitria; Dewi Mutmainnah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The Kampunge Arek Suroboyo Gender- and Child-Friendly (KAS-RPA) Program is an initiative launched by the Surabaya City Government to establish a child-friendly city through women's empowerment and child protection. This program focuses on various key indicators, including education, health, caregiving, safety, and creativity. This community service activity aims to provide assistance in the development of the KAS-RPA portfolio in RW 04, Gundih Sub-District, Bubutan District, Surabaya City, which serves as the designated community service site. The method employed in this community service program includes socialization of the KAS-RPA program to local cadres, followed by intensive consultations and discussions. The assistance process encompasses the identification of village potentials, collection of relevant documentation, and portfolio development in accordance with established guidelines. The outcome of this community service demonstrates the successful implementation of all KAS-RPA program indicators in RW 04, supported by the residents' favorable socio-economic awareness and educational background. This has resulted in a safe and comfortable living environment, with minimal occurrences of violations against children's rights or violence against women.In conclusion, the collaboration between facilitators and local cadres has proven effective in exploring and implementing the program's indicators. It is recommended that the program's coverage area be expanded and that similar activities be continuously conducted to maximize the program's positive impact throughout the city.